Enhancing Financial Independence of Micro and Small Enterprises Fostered by BMT Dana Mentari Muhammadiyah in Purwokerto - Rukoyah, Siti; Saepudin, Encep (Universitas Airlangga, 2025)
Baitul Maal wat Tamwil (BMT), as a sharia microfinance institution, plays an important role in enhancing the financial independence of Micro and small enterprises (MSEs). Common problems faced by these business actors include limited access to capital, minimal business assistance, and low understanding of financial management and marketing strategies. This study aims to explore how BMT Dana Mentari Muhammadiyah Purwokerto Karangwangkal strives to increase the financial independence of its members from the MSE sector. This study uses a qualitative descriptive approach (field research) with data collection techniques through interviews, direct observation, and documentation involving BMT administrators and members. The results of the study show that BMT's efforts to increase financial independence are carried out through three main programs: providing sharia-based financing, routine visits (silaturahmi) for business assistance and monitoring, and the